Novel Loop-Mediated Isothermal Amplification Method for Detection of the JP2 Clone of Aggregatibacter actinomycetemcomitans in Subgingival Plaque - Seki, Mitsuko (American Society for Microbiology (ASM), 2008)
We developed a loop-mediated isothermal amplification method that detects the JP2 clone of Aggregatibacter actinomycetemcomitans, which induces aggressive periodontitis in adolescents of North and West African descents. Being independent of special equipment, this specific and sensitive method offers significant advantages for screening of patients on a population basis and in clinical settings.